2018
DOI: 10.1155/2018/6014082
|View full text |Cite
|
Sign up to set email alerts
|

MHD Peristaltic Flow of Fractional Jeffrey Model through Porous Medium

Abstract: The magnetohydrodynamic (MHD) peristaltic flow of the fractional Jeffrey fluid through porous medium in a nonuniform channel is presented. The fractional calculus is considered in Darcy’s law and the constitutive relationship which included the relaxation and retardation behavior. Under the assumptions of long wavelength and low Reynolds number, the analysis solutions of velocity distribution, pressure gradient, and pressure rise are investigated. The effects of fractional viscoelastic parameters of the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…. (24) Here, I 0 and K 0 are modified Bessel functions of first and second kind of order 0 respectively,…”
Section: Analytical Solution For Low Zeta Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…. (24) Here, I 0 and K 0 are modified Bessel functions of first and second kind of order 0 respectively,…”
Section: Analytical Solution For Low Zeta Potentialsmentioning
confidence: 99%
“…Manzoor et al [23] obtained computational solutions for peristaltic pumping of magnetized rheological biofluids in ciliated conduits with thermal convection and permeability effects. Guo et al [24] analyzed trapping phenomena and wave amplitude effects in hydromagnetic pumping of viscoelastic fluids in porous media-filled tubes. AbdElmaboudet al [25] considered nonlinear viscosity variation in finite tube peristaltic pumping.…”
Section: Introductionmentioning
confidence: 99%
“…Peristalsis was first initiated by Latham in 1966. Furthermore, the research work was extended by Shapiro et al and Jaffrin et al Many researchers have been studied on both theoretical and practical aspects of peristaltic transport . The thermal energy vigorously depends on the temperature variation at the locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the research work was extended by Shapiro et al 2 and Jaffrin et al 3 Many researchers have been studied on both theoretical and practical aspects of peristaltic transport. [4][5][6][7] The thermal energy vigorously depends on the temperature variation at the locomotion. However, the energy transfer from one body to another body is depends on the This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.…”
mentioning
confidence: 99%
“…Hayat et al 38 perceived the outcomes of Joule heating, Hall current, and convective surface effects on peristalsis of viscous fluid through rotating enclosure. Guo et al 39 reported a fractional analysis of Jeffrey fluid MHD peristaltic transport in a permeable media. Peristalsis of Casson fluid in an inclined permeable enclosure under convective conditions was probed by Rajashekhar et al 40 Ahmed et al 41 investigated the mass and heat transfer mechanisms for magnetized micropolar flow through a curved channel established due to peristaltic waves.…”
Section: Introductionmentioning
confidence: 99%